1991
DOI: 10.1177/089431849100400308
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Health in the Oldest Old: A Phenomenological Study

Abstract: In the United States and in many other parts of the world, the fastest growing age group is 80 years and over. It is precisely in this oldest old age cohort that very little is known about the experience of health. The purpose of this study was to investigate the lived experience of health for the oldest old within the community through the use of the phenomenological method. While there has been some research on the personal experience of health, the meaning of these experiences has not been studied in the ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
0
8
0
2
Order By: Relevance
“…Analysis of the qualitative literature on aging and cancer experiences indicated that a struggle for life occurs in serious illnesses and that the struggle has direction, meaning, and is valued (Wagnild & Young, 1990;Wondelowsky & Davis, 1990). Meaning is described as essential to transcendence and transcendence to resilience, health, and well-being (Reed, 1991;Taylor, 1993Taylor, , 1995Thompson & Jannigan, 1988;Tien, 1991).…”
Section: Issues In the Literature Reviewmentioning
confidence: 95%
“…Analysis of the qualitative literature on aging and cancer experiences indicated that a struggle for life occurs in serious illnesses and that the struggle has direction, meaning, and is valued (Wagnild & Young, 1990;Wondelowsky & Davis, 1990). Meaning is described as essential to transcendence and transcendence to resilience, health, and well-being (Reed, 1991;Taylor, 1993Taylor, , 1995Thompson & Jannigan, 1988;Tien, 1991).…”
Section: Issues In the Literature Reviewmentioning
confidence: 95%
“…The second theme of the meaning of health, listening to energy flow, extends the idea of energy as activity offered by Perry and Wood's (1995) theme of energy as doing, Wondolowski and Davis's (1991) theme of abiding vitality centered on energy, and Parse, Coyne, and Smith's (1985) transcendent vitality as a feeling of energy. Listening to energy flow was the linchpin between the first and third themes that connected all themes together.…”
Section: Discussion Of Findingsmentioning
confidence: 92%
“…Wondolowski and Davis (1991) studied the lived meaning of health in men and women aged 80 to over 100. They found common elements of health emerging as abiding vitality, generating fulfillment and rhapsodic reverie.…”
Section: Background and Review Of The Literaturementioning
confidence: 99%
“…Rosenbaum's (1991) ethnographic techniques, including in-depth interviews lasting 1.5-4 hours and observation-participation, elicited rich data and facilitated an understanding of context relevant health meanings. Wondolowski and Davis (1991) employed van Kaam's modified phenomenology to explore the lived meaning of health of one-hundred and eight men and women over the age of eighty.^ In this study, three common elements surfaced from 411 descriptive expressions through a process of "intuiting and analyzing" (p. 115). Stevens and Hall (1988) chose open-ended questions and encouraged participants to speak o f the experiences of "lesbians in general" to generate data in van Kaam's phenom enology enabled such a large sample in part because "there is no provision for returning to the subject for an elaborated description" (1991, p. 115).…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…McCormack and Gooding (1993) found that homeless people express their health meanings in four distinct perceptions based on the unique combination of "physical, mental, emotional, spiritual, social, and environmental health dimensions" (p. 47). Elderly people in a phenomenological study by Wondolowski and Davis (1991) contributed profoundly unique meanings of health based on a psychological and metaphysical sense of being in the world (and not on health dimensions per se), including energetic self-affirmation, creating fulfillment, and the reverie associated with reminiscing and future projection.^ The inner city residents in Morse's study (1987) expressed their health meanings through different combinations of physical and mental (e.g. psychological and emotional) dimensions.…”
Section: General Health Domainsmentioning
confidence: 99%